Alcaligenes faecalis—a maize endophytic bacterium to reduce Stewart wilt disease - Syahri; Giyanto; Hamzah Mutaqin, Kikin (Agriculture and Natural Resources, 2025)
Importance of the work: Alcaligenes faecalis can effectively reduce Stewart wilt disease, one of the most important maize diseases. Objectives: To evaluate the effect of A. faecalis on the inhibition of Stewart wilt disease and growth enhancement of maize. Materials and Methods: Three potential isolates of A. faecalis (JCB-1, JCJ-7 and MS-X) were used to decrease the disease. The antagonistic activity, volatile organic compounds (VOCs) and growth-promoting activities were evaluated in vitro. The effectiveness of endophytes for stimulating maize growth was assessed using a seed germination test, while their ability to reduce the disease was tested on seedlings. The responsiveness of plant defense was detected by containing phenylalanine ammonia-lyase and polyphenol oxidase (PPO) in seedlings. In addition, the chemical compounds of the bacterial endophytes were identified using gas chromatography-mass spectrometry. Results: All the tested endophytic isolates could fix nitrogen, solubilize phosphate and produce indole. The A. faecalis MS-X isolate had the highest VOC activity (78.94%) and efficacy in reducing disease severity (52.4%), while the most significant antibiosis activity was produced by the isolate JCJ-7 (100%). In addition, the isolate MS-X had the best capacity to induce PPO, along with excellent ability to reduce pathogen infection and growth promoters, while JCB-1 effectively enhanced the germination of maize. Main finding: A. faecalis had the potential to reduce Stewart wilt diseases by both induction resistance and enhancing maize growth.